Composite silver plating method for aluminum base surface of electric contact component

By performing composite silver plating on the surface of aluminum-based electrical contact parts, including pre-copper layer and silver-graphene composite layer, the problems of overheating and contact resistance of aluminum-based electrical contact parts are solved, the conductivity improvement and cost reduction are achieved, and the stable operation of the power grid is ensured.

CN119824499APending Publication Date: 2025-04-15STATE GRID JIBEI ELECTRIC POWER CO LTD TANGSHAN POWER SUPPLY CO +2
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411717055.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

Aluminum-based electrical contact components have problems such as overheating and large contact resistance in power transmission and transformation equipment, resulting in surface burning and welding morphology, which may be burned in severe cases. The existing treatment methods have limitations, high costs and unstable costs.

Method used

The aluminum-based surface composite silver plating method is adopted, including surface treatment of the aluminum-based surface of the electrical contact parts, pre-plating copper layer and silver-graphene composite layer to generate an aluminum-based copper-silver-graphene composite coating, improving conductivity and binding force, and reducing contact resistance.

Benefits of technology

It effectively reduces the contact resistance of aluminum-based electrical contact parts, improves conductivity, reduces overheating, reduces the cost of heat treatment in substations, and ensures long-term, safe and stable operation of the power grid.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention provides a composite silver plating method for an aluminum-based surface of an electric contact part. The method comprises the following steps: carrying out surface treatment on the aluminum-based surface of the electric contact part; pre-plating a copper layer on the surface of the aluminum base of the electric contact component subjected to surface treatment; and plating a silver-graphene composite layer on the aluminum-based surface of the electric contact component after the copper layer pre-plating is completed. According to the technical scheme provided by the invention, the surface of the aluminum base is pre-plated with the copper layer and then plated with the silver-graphene composite layer to generate the aluminum base-copper-silver-graphene composite plating layer, so that silver plating of the aluminum base is effectively realized, and the problem that silver plating on the surface of the aluminum base is difficult is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electric contact material preparation, and in particular relates to a composite silver plating method for an aluminum-based surface of an electric contact component for power transmission and transformation equipment. Background Art

[0002] At present, there are a large number of aluminum-based electrical contact components for power transmission and transformation equipment in the power grid, such as terminal boards, conductive rods, etc. Aluminum-based electrical contact components generally have problems such as overheating and excessive contact resistance, which will cause obvious burning and welding morphology on the surface of these electrical contact components, and even burn them in serious cases. The main reason for the heating of aluminum-based electrical contact components is that surface corrosion, wear, shedding, etc. cause the contact resistance to increase, resulting in a sudden increase in heat generation at the contact part.

[0003] At present, the heat treatment methods of aluminum-based electrical contact components of power transmission and transformation equipment mainly include the following categories:

[0004] (1) After the aluminum-based terminal board overheats, the corrosion products are removed and the surface is polished. This method can reduce the contact resistance of the terminal board and slow down the heating of the electrical contact parts to a certain extent. However, it has great limitations: it is handled after the equipment fails, and the active support is insufficient; the frequency of treatment is too high, and the number of hot spots to be treated is large. There are hundreds of aluminum-based hot spots in a 110kV substation, and the labor and cost are too high.

[0005] (2) After the aluminum-based terminal board is overheated, it is treated with conductive paste. This method can increase the conductivity of the electrical contact parts, reduce the contact resistance, and slow down the overheating phenomenon, but it will bring new problems. The conductive paste is sticky after application and will absorb particulate matter and corrosive particles in the atmosphere, resulting in the formation of a microscopic corrosive environment on the electrical contact surface, which may cause crevice corrosion and oxygen concentration corrosion. Particles with higher hardness will increase the wear of the electrical contact surface, and the contact resistance will increase instead of decrease after a period of time.

[0006] (3) After the aluminum-based terminal board overheats, the terminal board components are replaced; this method can solve the overheating problem of the electrical contact point, but it will lead to high substation operation and maintenance costs. At the same time, the replacement of equipment requires power outage processing, resulting in a sudden increase in the frequency of power outages in the station, which is not conducive to the stable operation of the power grid;

[0007] (4) Silver plating on aluminum substrates: Silver plating is performed on the aluminum substrate electrical contact surface. Silver has good conductivity. After silver plating, the conductivity of the electrical contact parts is greatly improved, which reduces the contact resistance of the aluminum substrate electrical contact parts, reduces the frequency and period of overheating of the aluminum substrate electrical contact parts, reduces the cost of heat treatment in substations, and ensures the long-term, safe and stable operation of the power grid. However, there are many difficulties in the current aluminum substrate surface silver plating technology: aluminum and its alloys have a strong affinity for oxygen, and an oxide film is easily formed on the surface. This oxide film will affect the bonding strength of the silver plating layer; aluminum is an amphoteric metal and easily reacts with acids and alkalis, causing corrosion of parts and making silver electroplating difficult; aluminum has a larger expansion coefficient than many metals. When the ambient temperature changes, due to the inconsistency between its expansion coefficient and the silver plating layer, internal stress is easily generated, making the silver plating layer easy to peel off from the substrate; the bonding strength between the silver plating layer and the aluminum substrate is low, and special treatment methods, such as chemical zinc immersion, are required to improve the bonding strength between the silver plating layer and the aluminum substrate metal; the silver plating layer is easily oxidized.

[0008] In summary, the development of aluminum-based composite silver-plated electrical contact components is of great significance for the heat management of power transmission and transformation equipment and ensuring the safe and stable operation of the power grid. At present, it is still necessary to study technical solutions that can effectively realize aluminum-based silver plating. Summary of the invention

[0009] The purpose of the present invention is to provide a technical solution that can effectively realize aluminum-based silver plating, so as to reduce the contact resistance of aluminum-based electrical contact components, improve their electrical conductivity, and solve the over-temperature and overheating phenomenon.

[0010] In order to achieve the above object, the present invention provides a method for composite silver plating on an aluminum-based surface of an electrical contact component, wherein the method comprises:

[0011] Surface treatment of the aluminum-based surface of the electrical contact component;

[0012] Pre-plating a copper layer on the aluminum-based surface of the electrical contact component that has undergone surface treatment;

[0013] The silver-graphene composite layer is plated on the aluminum-based surface of the electrical contact component that has been pre-plated with a copper layer.

[0014] The technical solution provided by the present invention is to pre-plate a copper layer on the surface of an aluminum substrate and then plate a silver-graphene composite layer to generate an aluminum-copper-silver-graphene composite coating, thereby effectively realizing aluminum-based silver plating and solving the problem of difficulty in silver plating on the aluminum-based surface.

[0015] According to a specific embodiment of the method for composite silver plating on an aluminum-based surface of an electrical contact component, preferably, surface treatment of the aluminum-based surface of the electrical contact component comprises:

[0016] The aluminum-based surface of the electrical contact component is subjected to grinding, etching, electro-cleaning and activation treatment in sequence;

[0017] Grinding treatment can effectively remove surface dirt and oxides to ensure a bright and rust-free surface; etching treatment can produce slight etching on the surface, which is conducive to improving the adhesion between the substrate surface and the coating; electro-cleaning treatment can dissolve grease and oil stains on the surface; activation treatment can remove the oxide film and fatigue layer on the substrate surface;

[0018] More preferably, the grinding process includes: coarse grinding, fine grinding and polishing in sequence; further preferably, the coarse grinding is performed using 800# sandpaper, the fine grinding is performed using 1000# sandpaper, and the polishing is performed using 1200# sandpaper;

[0019] More preferably, the etching treatment includes sequentially performing a hydrochloric acid soaking treatment and an alkaline solution soaking treatment; further preferably, the hydrochloric acid soaking treatment includes sequentially using hydrochloric acid with a HCl mass concentration of 50% to soak at 60°C for 5-10min and at 70°C for 5-10min; further preferably, the raw material composition of the alkaline solution used in the alkaline solution soaking treatment includes NaOH, Na2SO4, Na2CO3, Na2SiO3 and water; based on the volume of the alkaline solution, the content of NaOH is 2-5g·L -1 , the content of Na2SO4 is 35-55g·L -1 , the content of Na2CO3 is 30-50g·L -1 , the content of Na2SiO3 is 10-20g·L -1 ;

[0020] More preferably, the working voltage of the electro-cleaning treatment is 8-12V and the working time is 30-40s;

[0021] More preferably, the raw material composition of the electro-cleaning liquid used in the electro-cleaning treatment includes sodium hydroxide, sodium carbonate, sodium phosphate, sodium silicate and water; based on the volume of the electro-cleaning liquid, the content of sodium hydroxide is 10-45g·L -1 , the content of sodium carbonate is 11-18g·L -1 , the content of sodium phosphate is 25-35g·L -1 , the content of sodium silicate is 2-15g·L -1 ;

[0022] More preferably, the activation treatment has an operating voltage of -12V to -8V and a working time of 30-40s;

[0023] More preferably, the raw material composition of the activation solution used in the activation treatment includes hydrochloric acid, sodium chloride and water; based on the volume of the activation solution, the content of hydrochloric acid is 15-30g·L -1 , the content of sodium chloride is 110-145g·L -1 .

[0024] According to the specific implementation of the method for composite silver plating on the aluminum-based surface of an electrical contact component, preferably, the pre-plated copper layer is carried out by brush plating;

[0025] More preferably, the raw material composition of the electroplating solution used for the pre-copper plating layer includes: CuSO4·5H2O, H2SO4, CuCl2 and solvent; based on the volume of the electroplating solution, the content of CuSO4·5H2O is 150-180g·L -1 , H2SO4 content is 75-95g·L -1 , CuCl2 content is 0.05-0.15g·L -1 ;

[0026] Further preferably, the solvent used in the electroplating solution used for the pre-copper plating layer is water;

[0027] Further preferably, during the pre-copper plating process, the working voltage of the brush plating is 6-8V, and the relative movement speed between the brush plating pen and the workpiece is 2-4m·min -1 , current density is 0.1-0.5A·dm -2 The electroplating time is 2-4 minutes, and the time is determined according to the required copper plating layer thickness.

[0028] According to a specific implementation of the method for composite silver plating on an aluminum-based surface of an electrical contact component, preferably, the thickness of the copper layer is 18-25 μm.

[0029] According to the specific implementation of the method for composite silver plating on the aluminum-based surface of an electrical contact component, preferably, the silver-graphene composite layer is plated by brush plating;

[0030] More preferably, the raw material composition of the electroplating solution used for plating the silver-graphene composite layer includes: silver nitrate, succinimide, potassium pyrophosphate, graphene and solvent; based on the volume of the electroplating solution, the content of silver nitrate is 30-50g·L -1 , the content of succinimide is 20-30g·L -1 , graphene content is 5-30g·L -1 , the content of potassium pyrophosphate is 30-50g·L -1 ; Succinimide mainly acts as a complexing agent and brightener, and potassium pyrophosphate acts as a surfactant, which is more conducive to the combination of modified graphene and silver. The composite coating obtained by this electroplating solution is bright and has good bonding strength;

[0031] Further preferably, during the process of plating the silver-graphene composite layer, the working voltage of the brush plating is 3-5V, and the relative movement speed between the brush plating pen and the workpiece is 2-4m·min -1 , current density is 0.1-0.5A·dm -2, the electroplating time is 2-4 minutes, and the specific time is determined according to the required thickness of the silver-plated layer; the preferred method is to further reduce the agglomeration of silver nanoparticles and improve their uniform dispersion on the graphene surface by controlling the brush plating conditions;

[0032] More preferably, the solvent is water;

[0033] Further preferably, the graphene is modified by a silane coupling agent; more preferably, the silane coupling agent is KH570 silane coupling agent (i.e., γ-methacryloxypropyltrimethoxysilane), and its siloxane group reacts with the hydroxyl group on the graphene to form a silicon-oxygen bond, thereby connecting KH570 to the graphene surface; in a specific embodiment, the silane coupling agent modified graphene is prepared by the following method: dispersing graphene oxide in water to prepare a graphene oxide suspension; mixing the graphene oxide suspension, the silane coupling agent and water, adjusting the pH value to 10, obtaining a reaction system, and heating the reaction system at 70° C. to prepare silane coupling agent modified graphene; in a specific embodiment, the graphene oxide is prepared by the Hummers method;

[0034] During the electrical phenomenon, larger particles are formed, which will cause the conductivity of graphene to decrease and affect its application in electronic devices; due to the different interaction forces between silver nanoparticles and the graphene surface, the silver nanoparticles will be unevenly distributed on the graphene surface, which will affect the conductivity and stability of graphene; the active sites on the graphene surface are limited, which may lead to poor uniform dispersion of silver nanoparticles; silver nanoparticles are easily oxidized in the air, reducing their conductivity; in a preferred embodiment of the present invention, succinimide is selected as a complexing agent and potassium pyrophosphate is used as a surfactant to reduce the agglomeration of silver nanoparticles, improve the uniform dispersion of silver nanoparticles on the graphene surface, prevent the oxidation of silver nanoparticles and improve their chemical stability; in a preferred embodiment of the present invention, graphene is modified with a silane coupling agent to increase the active sites on the graphene surface, reduce the agglomeration of silver nanoparticles, improve the uniform dispersion of silver nanoparticles on the graphene surface, improve the dispersibility of graphene and its compatibility with the polymer matrix, and improve the performance of the composite coating.

[0035] According to the specific implementation method of the composite silver plating method for the aluminum-based surface of an electrical contact component, brush plating is performed using a brush plating machine. First, the substrate to be brush plated is connected to the negative electrode of a power supply as a cathode, and the brush plating pen (with a sheath) connected to the positive electrode of the power supply is immersed in the plating solution as an anode. Relying on the action of direct current, the brush plating pen maintains contact with the workpiece under a certain pressure and performs relative movement during brush plating. The metal cations in the plating solution in the bath are discharged and crystallized on the substrate to be brush plated as the cathode to form a coating. After the brush plating is completed, rinse with water, then rinse with alcohol, and finally blow dry. The high-frequency mechanical vibration of an ultrasonic cleaner is used to clean the oil wrapped on the surface of the sample, the adhered impurities, and the attached fingerprints.

[0036] According to a specific implementation of the method for composite silver plating on an aluminum-based surface of an electrical contact component, preferably, the thickness of the silver-graphene composite layer is 30-37.5 μm.

[0037] According to the specific implementation of the method for composite silver plating on the aluminum-based surface of an electrical contact component, preferably, the method for composite silver plating on the aluminum-based surface of an electrical contact component further comprises: performing electrolytic passivation treatment on the aluminum-based surface of the electrical contact component after the silver-graphene composite layer is plated; thereby improving the anti-discoloration ability of the silver plating layer;

[0038] More preferably, the composite silver plating method for the aluminum-based surface of the electrical contact component further comprises: testing the anti-discoloration ability of the coating on the aluminum-based surface of the electrical contact component with ammonium sulfide;

[0039] More preferably, the composite silver plating method for the aluminum-based surface of the electrical contact component further comprises: using a thermal shock method to detect the bonding strength of the coating on the aluminum-based surface of the electrical contact component;

[0040] Using ammonium sulfide to test the coating's ability to resist discoloration and thermal shock testing to test the coating's bonding strength can effectively prevent unqualified products from entering the next process.

[0041] The technical solution provided by the technical solution of the present invention can effectively realize the composite silver plating on the aluminum-based surface of the electrical contact components of the power transmission and transformation equipment, improve the conductivity of the aluminum-based components, reduce the contact resistance of the aluminum-based electrical contact components, reduce the frequency and period of overheating of the aluminum-based electrical contact components, reduce the cost of heat treatment in substations, and ensure the long-term, safe and stable operation of the power grid. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] Figure 1 Schematic diagram of the Tafel polarization curves of the pure silver coating of Comparative Example 1 and the composite coating of Example 1.

[0043] Figure 2 Schematic diagram of the Tafel polarization curves of the composite coatings of Example 1, Example 4, and Example 7.

[0044] Figure 3Schematic diagram of the Tafel polarization curves of the composite coatings of Example 1, Example 2, and Example 3.

[0045] Figure 4 Schematic diagram of the equivalent circuit for impedance spectroscopy test.

[0046] Figure 5 It is the Nyquist diagram of impedance diagram spectrum of the composite coating of Example 1 to Example 9.

[0047] Figure 6 It is a Bode modulus diagram of impedance schematic spectrum of the composite coating of Example 1 to Example 9.

[0048] Figure 7 It is the impedance schematic spectrum phase angle diagram of the composite coating of Example 1 to Example 9.

[0049] Figure 8 This is a cross-sectional morphology diagram of the composite coating of Example 2.

[0050] Fig. 9 This is a cross-sectional morphology diagram of the composite coating of Example 5.

[0051] Fig.10 This is a cross-sectional morphology of the composite coating of Example 8.

[0052] Fig.11 Surface microscopic morphology of the composite coatings of Examples 1 to 9.

[0053] Fig.12 It is a schematic diagram of the surface morphology analysis of the composite coatings of Example 1, Example 2, Example 4, Example 7, and Example 8.

[0054] Fig.13 Schematic diagram of graphene modification.

[0055] Fig.14 This is the SEM image of graphene modified with silane coupling agent.

[0056] Fig.15 This is the SEM image of the graphene oxide sample.

[0057] Fig.16 This is a picture of the coating of Example 1.

[0058] Fig.17 This is a picture of the coating of Comparative Example 4. DETAILED DESCRIPTION

[0059] In order to make the purpose, technical solution and advantages of the embodiment of the present invention clearer, the technical solution in the embodiment of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiment of the present invention. Obviously, the described embodiment is a part of the embodiment of the present invention, not all of the embodiments. Based on the embodiment of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work belong to the protection scope of the present invention.

[0060] Example 1

[0061] This embodiment provides a method for composite silver plating on an aluminum-based surface of an electrical contact component, wherein the method comprises:

[0062] 1. Surface treatment of the aluminum-based surface of the electrical contact parts, including:

[0063] The aluminum-based surface of the electrical contact component is subjected to grinding, etching, electro-cleaning and activation treatment in sequence;

[0064] The grinding process includes: coarse grinding, fine grinding and polishing in sequence; coarse grinding is performed using 800# sandpaper, fine grinding is performed using 1000# sandpaper, and polishing is performed using 1200# sandpaper;

[0065] The etching treatment includes sequentially performing hydrochloric acid soaking treatment and alkaline solution soaking treatment; the hydrochloric acid soaking treatment includes sequentially using hydrochloric acid with a HCl mass concentration of 50% for soaking at 60°C for 10 minutes and soaking at 70°C for 10 minutes; the alkaline solution soaking treatment uses an alkaline solution of a mixture of NaOH, Na2SO4, Na2CO3, Na2SiO3 and water; based on the volume of the alkaline solution, the content of NaOH is 3g·L -1 , the content of Na2SO4 is 45g·L -1 , the content of Na2CO3 is 40g·L -1 , the content of Na2SiO3 is 15g·L -1 ;

[0066] The electro-cleaning liquid used in the electro-cleaning treatment is a mixture of sodium hydroxide, sodium carbonate, sodium phosphate, sodium silicate and water; based on the volume of the electro-cleaning liquid, the content of sodium hydroxide is 25g·L -1 , the content of sodium carbonate is 15g·L -1 , the content of sodium phosphate is 30g·L -1 , the content of sodium silicate is 15g·L -1 ; The working voltage of the electric cleaning treatment is 10V, and the working time is 30s;

[0067] The activation solution used in the activation treatment is a mixture of hydrochloric acid, sodium chloride and water; based on the volume of the activation solution, the content of hydrochloric acid is 20g·L-1 , the content of sodium chloride is 120g·L -1 ; The working voltage of the activation treatment is -10V and the working time is 30s.

[0068] 2. Pre-plating a copper layer on the aluminum-based surface of the electrical contact parts that have completed surface treatment by brush plating;

[0069] The electroplating solution used for the pre-copper plating layer is a mixture of CuSO4·5H2O, H2SO4, CuCl2 and water; based on the volume of the electroplating solution, the content of CuSO4·5H2O is 150g·L -1 , the content of H2SO4 is 75g·L -1 , CuCl2 content is 0.05g·L -1 The working voltage of brush plating is 6V, and the relative movement speed between the brush plating pen and the workpiece is 2m / min -1 , the current density is 0.4A·dm -2 , the electroplating time is 2min; the thickness of the copper layer is 20μm.

[0070] 3. The aluminum-based surface of the electrical contact component that has been pre-plated with a copper layer is plated with a silver-graphene composite layer by brush plating;

[0071] The plating solution used for the silver-graphene composite layer is a mixture of silver nitrate, succinimide, potassium pyrophosphate, graphene and water; based on the volume of the plating solution, the content of silver nitrate is 40g·L -1 , the content of succinimide is 25g·L -1 , the graphene content is 25g·L -1 , the content of potassium pyrophosphate is 40g·L -1 The working voltage of brush plating is 3V, and the relative movement speed between the brush plating pen and the workpiece is 2m / min -1 , the current density is 0.4A·dm -2 , the electroplating time is 2 min; the thickness of the obtained silver-graphene composite layer is 30 μm.

[0072] Among them, the graphene is graphene modified by a silane coupling agent; the graphene modified by a silane coupling agent is prepared specifically by the following method:

[0073] Graphene oxide was prepared by Hummers method: first, 2g graphite, 1g NaNO3, and 46mL H2SO4 (98% mass concentration) concentrated sulfuric acid were mixed and placed in an ice water bath and stirred for 30min to fully mix; 6g KMnO4 was weighed and added to the mixed product in portions, and the mixture was stirred for 2h and then moved into a 35°C warm water bath and stirred for 30min; then 92mL of distilled water was slowly added, and the mixture was placed at 98°C for 15min, and then a small amount of H2O2 (30% mass concentration) hydrogen peroxide was added to remove excess oxidant, and then 140mL of distilled water was added to dilute, filtered while hot, and then 0.01mol·L HCI was used in turn. -1 The graphene oxide was prepared by washing with hydrochloric acid, anhydrous ethanol and deionized water until there was no sulfate in the filtrate; the prepared graphene oxide was ultrasonically dispersed in water to obtain a graphene oxide dispersion; the graphene oxide dispersion was dried in a vacuum drying oven at 60°C for 48 hours to obtain a graphene oxide sample, which was stored for later use. The SEM image of the graphene oxide sample is shown in FIG. Fig.15 shown.

[0074] Graphene oxide modification (see Fig.13 ): 5g of graphene oxide sample was ultrasonically dispersed in 200mL of water to prepare graphene oxide suspension; 5g of graphene oxide suspension and 1.24g of KH-570 silane coupling agent were added to 200mL of deionized water, and the pH value was adjusted to 10 with a NaOH solution having a NaOH concentration of 0.1mol / L to obtain a mixed solution; then, the mixed solution was heated at 70°C for 4h under stirring conditions of 200r / min to prepare silane coupling agent modified graphene. The SEM image of silane coupling agent modified graphene is shown in FIG. Fig.14 shown.

[0075] 4. Perform electrolytic passivation treatment on the aluminum-based surface of the electrical contact component that has been plated with the silver-graphene composite layer; perform an ammonium sulfide anti-discoloration test on the coating on the aluminum-based surface of the electrical contact component, and perform a bonding strength test using a thermal shock method.

[0076] The obtained coating is Fig.16 shown.

[0077] Example 2

[0078] This embodiment provides a method for composite silver plating on an aluminum-based surface of an electrical contact component.

[0079] The only difference from Example 1 is that in the process of plating the silver-graphene composite layer on the aluminum-based surface of the electrical contact component that has completed the pre-copper plating layer by brush plating, the electroplating time is 3 minutes; and the thickness of the obtained silver-graphene composite layer is 32 μm.

[0080] Example 3

[0081] This embodiment provides a method for composite silver plating on an aluminum-based surface of an electrical contact component.

[0082] The only difference from Example 1 is that in the process of plating the silver-graphene composite layer on the aluminum-based surface of the electrical contact component that has completed the pre-copper plating layer by brush plating, the electroplating time is 4 minutes; and the thickness of the obtained silver-graphene composite layer is 37.5 μm.

[0083] Example 4

[0084] This embodiment provides a method for composite silver plating on an aluminum-based surface of an electrical contact component.

[0085] The only difference from Example 1 is that in the process of plating the silver-graphene composite layer on the aluminum-based surface of the electrical contact component that has completed the pre-copper plating layer by brush plating, the plating pressure is 4V; the thickness of the obtained silver-graphene composite layer is 35μm.

[0086] Example 5

[0087] This embodiment provides a method for composite silver plating on an aluminum-based surface of an electrical contact component.

[0088] The only difference between it and Example 4 is that: in the process of plating the silver-graphene composite layer on the aluminum-based surface of the electrical contact component that has completed the pre-copper plating layer by brush plating, the electroplating time is 3 minutes; the thickness of the obtained silver-graphene composite layer is 32 μm.

[0089] Example 6

[0090] This embodiment provides a method for composite silver plating on an aluminum-based surface of an electrical contact component.

[0091] The only difference between it and Example 4 is that: in the process of plating the silver-graphene composite layer on the aluminum-based surface of the electrical contact component that has completed the pre-copper plating layer by brush plating, the electroplating time is 4 minutes; the thickness of the obtained silver-graphene composite layer is 36 μm.

[0092] Example 7

[0093] This embodiment provides a method for composite silver plating on an aluminum-based surface of an electrical contact component.

[0094] The only difference from Example 1 is that in the process of plating the silver-graphene composite layer on the aluminum-based surface of the electrical contact component that has completed the pre-copper plating layer by brush plating, the plating pressure is 5V; the thickness of the obtained silver-graphene composite layer is 34μm.

[0095] Example 8

[0096] This embodiment provides a method for composite silver plating on an aluminum-based surface of an electrical contact component.

[0097] The only difference between it and Example 7 is that: in the process of plating the silver-graphene composite layer on the aluminum-based surface of the electrical contact component that has completed the pre-copper plating layer by brush plating, the electroplating time is 3 minutes; the thickness of the obtained silver-graphene composite layer is 34 μm.

[0098] Example 9

[0099] This embodiment provides a method for composite silver plating on an aluminum-based surface of an electrical contact component.

[0100] The only difference between it and Example 7 is that: in the process of plating the silver-graphene composite layer on the aluminum-based surface of the electrical contact component that has completed the pre-copper plating layer by brush plating, the electroplating time is 4 minutes; the thickness of the obtained silver-graphene composite layer is 37.5 μm.

[0101] Comparative Example 1

[0102] This comparative example provides a method for composite silver plating on an aluminum-based surface of an electrical contact component.

[0103] The difference between it and Example 1 is that: (1) no pre-copper plating layer is performed; (2) a silver layer is plated by brush plating instead of a silver-graphene composite layer; specifically, the only difference from Example 1 is that the raw material composition of the electroplating solution used does not contain graphene.

[0104] Comparative Example 2

[0105] This comparative example provides a method for composite silver plating on an aluminum-based surface of an electrical contact component.

[0106] The only difference between it and comparative example 1 is that in the process of plating the silver-graphene composite layer on the aluminum-based surface of the electrical contact component that has been pre-plated with a copper layer by brush plating, the plating pressure is 4V.

[0107] Comparative Example 3

[0108] This comparative example provides a method for composite silver plating on an aluminum-based surface of an electrical contact component.

[0109] The only difference between it and comparative example 1 is that in the process of plating the silver-graphene composite layer on the aluminum-based surface of the electrical contact component that has been pre-plated with a copper layer by brush plating, the plating pressure is 5V.

[0110] Comparative Example 4

[0111] This comparative example provides a method for composite silver plating on an aluminum-based surface of an electrical contact component.

[0112] The only difference between this embodiment and Example 1 is that the raw material composition of the electroplating solution used in the process of plating the silver-graphene composite layer on the aluminum-based surface of the electrical contact component that has been pre-plated with a copper layer by electro-brush plating does not contain succinimide.

[0113] The coating obtained in this comparative example is as follows Fig.17 shown.

[0114] Experimental Example 1

[0115] The hardness of the composite coatings (copper-silver-graphene coatings) prepared in Examples 1 to 9 were tested respectively.

[0116] During the hardness test, 5 points are randomly selected for hardness testing on each sample to be tested, and the average value of the hardness test results of the 5 points is taken as the hardness of the sample to be tested.

[0117] The results are shown in Table 1.

[0118] Table 1

[0119]

[0120] From the comparison of the hardness of the composite coating under different process conditions in Table 1, it can be seen that: under the condition of constant brush plating time, with the increase of brush plating voltage, the hardness increases significantly, which plays a role in surface strengthening and also improves the wear resistance of the substrate to a certain extent; when the brush plating voltage is the same, with the increase of brush plating time, the coating becomes thicker, and the hardness of the composite coating will increase significantly, but too long brush plating time will lead to a large coating thickness, causing excessive stress, thereby affecting the hardness of the coating.

[0121] Experimental Example 2

[0122] The composite coatings (copper-silver-graphene coatings) prepared in Examples 1 to 9 and the pure silver coatings prepared in Comparative Examples 1 to 3 were tested for electrochemical parameters.

[0123] Specifically test the potentiodynamic polarization curve, self-corrosion potential, self-corrosion current density and impedance (the equivalent circuit of impedance test is as follows Figure 4 shown).

[0124] The self-corrosion potential and self-corrosion current density are shown in Table 2. The potential polarization curve is shown in Figure 1 , Figure 2 , Figure 3 The impedance test results are shown in Figure 5 , Figure 6 , Figure 7 shown.

[0125] Table 2

[0126]

[0127]

[0128] The potentiodynamic polarization curves of the pure silver coating of Comparative Example 1 and the composite coating of Example 1 in 3.5% NaCl solution are shown in FIG. Figure 1As shown. For electrochemical corrosion, the self-corrosion potential can explain the corrosion tendency of the alloy, and the self-corrosion current density can be used to indicate its corrosion rate. Compared with the pure silver coating, the potentiodynamic polarization curve of the composite coating in 3.5% NaCl solution shows a lower self-corrosion potential, which indicates that the potential for the start of corrosion is more negative, that is, it is easier to start corrosion. The self-corrosion current density of the composite coating is smaller than that of the pure silver coating, which means that the corrosion rate is slower, indicating that the corrosion resistance of the composite coating has improved. This phenomenon can be attributed to the addition of graphene. Graphene and silver are co-deposited into the composite coating, which not only increases the density of the coating, but also because of the chemical stability and high hydrophobicity of graphene itself, it can effectively cover the surface of the grains and properly isolate the direct contact between the corrosive medium and the grains or grain boundaries. Thereby improving the corrosion resistance of the composite coating. The potentiodynamic polarization curves of the composite coating in 3.5% NaCl solution under different brush plating voltages are shown in Figure 2 As shown in the figure, it can be found that within the same brush plating time, when the brush plating voltage is 3V, the corrosion potential of the coating is the most positive and the corrosion tendency is the smallest; for the corrosion current density, it is also the smallest when the brush plating voltage is 3V, indicating that when the brush plating voltage is 3V, the corrosion resistance of the sample is the best. The potentiodynamic polarization curves of the silver-graphene composite coating in 3.5% NaCl solution under different brush plating times are shown in the figure. Figure 3 As shown, it can be found that under the same brush plating voltage, the longer the brush plating time, the greater the corrosion tendency and the faster the corrosion, so at 2 minutes, the corrosion resistance of the sample is the best.

[0129] The Nyquist diagram was drawn based on the impedance spectrum test results of the composite coating (the results are shown in Figure 5 ) and Bode plots (results as shown Figure 6 , Figure 7 The Nyquist plot is a plot of the imaginary part of impedance (-Z") versus the real part of impedance (Z'). The larger the radius of the arc in the plot, the greater the polarization resistance and the better the corrosion resistance. Figure 5 It can be seen that the composite coating exhibits a higher impedance value when the brush plating voltage is 3V and the brush plating time is 2min and 3min. It can be inferred that the samples under these two process conditions have good corrosion resistance. Figure 6 (Logarithmic graph of Bode impedance modulus |Z| and frequency f) It can be observed that the impedance modulus of the composite coating in the low-frequency region is relatively high when the brush plating voltage is 3V and the brush plating time is 2min and 3min. At present, the lowest frequency impedance modulus (|Z|0.01Hz) is generally used as the standard for evaluating the protective performance of the coating. The higher the value of |Z|0.01Hz, the better the corrosion resistance, and vice versa. Therefore, the change trend of |Z|0.01Hz is consistent with the phenomenon reflected in the Nyquist diagram. Figure 7(The logarithmic graph of Bode phase angle and frequency) also shows that the phase angle of the coating when the brush plating voltage is 3V and the brush plating time is 2min and 3min is significantly higher than that of the coating under other process conditions, indicating that the composite coating has better corrosion resistance when the brush plating voltage is 3V and the brush plating time is 2min and 3min.

[0130] Experimental Example 3

[0131] The cross-sectional morphologies of the composite coatings prepared in Examples 1 to 9 were observed respectively to determine the thickness of the composite coatings.

[0132] Among them, the cross-sectional morphology of Example 2 is as follows Figure 8 As shown, the cross-sectional morphology of Example 5 is as follows Fig. 9 As shown, the cross-sectional morphology of Example 8 is as follows Fig.10 shown.

[0133] When the brush plating time is 3 min, the cross-sectional morphology of the composite coating under different brush plating voltages (such as Figure 8 , Fig. 9 , Fig.10 As shown in the figure, it can be seen that the thickness of the composite coating can reach more than 30μm, and the coating under 3V conditions can reach 37.5μm. The cross-sectional view also shows that the thickness is relatively uniform, which proves that the brush plating effect is good.

[0134] Experimental Example 4

[0135] The surface morphologies of the composite coatings prepared in Examples 1 to 9 were observed respectively.

[0136] The results are as follows Fig.11 As shown, Fig.11 In the figure, a, b, c, d, e, f, g, h, and i are the surface morphologies of the composite coatings of Examples 1 to 9, respectively. Fig.11 Fig. j is the surface morphology of the composite coating of Example 4 magnified 20,000 times.

[0137] Fig.11 In the figure, a, b, and c are the surface micromorphologies of the composite coatings with different brush plating voltages under the same brush plating time. It can be seen that with the increase of voltage, the nucleation rate increases, the grain size decreases, the gaps between the coating grains gradually decrease, and the coating surface becomes smooth and dense. Fig.11 In the figure, b, e, and h are the surface microstructures of the samples with different brush plating times under the same brush plating voltage. It can be seen that the coating becomes denser with the extension of time.

[0138] Fig.11 The bright substances in d and g may be impurities, indicating that the bonding strength of the composite coating under these two conditions is not good enough, and there is a gap in the middle, allowing the outside atmosphere to enter the gap and combine with the substrate to form this round substance. Fig.11 It can be seen from the figure that the grain distribution of the composite coating is uneven under the conditions of brush plating voltage 5V and brush plating time 4min. Fig.11 Further increase the magnification of a certain area in b, and get Fig.11 The microscopic morphology of the composite coating in Figure 1. It can be found that there are nearly transparent flakes in the middle area, interspersed between the cells, and the morphology is very similar to the graphene used.

[0139] Experimental Example 5

[0140] The surface morphologies of the composite coatings prepared in Example 1, Example 2, Example 4, Example 7, and Example 8 were observed respectively.

[0141] The results are as follows Fig.12 shown. Fig.12 In the figure, a, b, c, d, and e are the surface morphologies of the composite coatings of Example 1, Example 4, Example 7, Example 2, and Example 8, respectively.

[0142] Fig.12 The following are the surface morphologies of the composite coatings obtained at different current densities. At low current density, the cathode overpotential is small, the surface active sites are few, the probability of coating nuclei formation is small, and the formation speed is slow. The graphite particles adsorbed on the cathode surface are difficult to be coated with silver in time to achieve co-deposition. Fig.12 In a, we can clearly see the graphite flakes embedded in the coating but not completely covered. At this time, the corresponding composite coating is relatively sparse, thin, and contains less graphite particles. As the current density increases, the polarization of the cathode increases, increasing the deposition overpotential, accelerating the deposition rate of silver, and effectively covering the graphite particles. The thickness and density of the composite coating gradually increase, as shown in Figure 1. Fig.12 As shown in b, c, and d. Fig.12 Where c is the current density 0.3A / dm 2 The composite coating prepared under this condition has a thickness of 6.68μm at this time, and the coating is much denser than that at low current density. It can also be seen that there are many pores in the composite coating, which is because the graphite flakes restrict the normal growth of silver during the co-deposition process. However, the higher the current density, the better. At high current density, the speed at which silver ions diffuse to the vicinity of the cathode is lower than their consumption rate, resulting in severe concentration polarization. Once the current density approaches or exceeds the limiting current density, the cathode is severely lacking in discharge metal ions, the surface hydrogen evolution rate increases, and the pH value near the cathode rises rapidly, resulting in reduced current efficiency. The metal ions begin to discharge at the edge and tip where the current density is higher, and the coating morphology becomes rough and even burns and blackens. Taking all factors into consideration, the current density is controlled to be 0.3A / dm 2 At this time, the electrodeposition rate is faster and the composite coating is denser.

[0143] Experimental Example 6

[0144] The dispersibility of the silane coupling agent-modified graphene used in the examples and the graphene oxide used to prepare the silane coupling agent-modified graphene in the electroplating solution was tested respectively.

[0145] The plating solution for the silver-plated-graphene composite layer is prepared by using graphene modified by silane coupling agent and graphene oxide respectively according to the raw material composition of the plating solution in Example 1. The unoxidized graphene is not completely integrated into the plating solution, and stratification occurs, resulting in poor bonding effect. However, the graphene modified by silane coupling agent has good dispersibility in the plating solution.

[0146] The embodiments described above are for better explaining the present invention. For technical researchers in the field, it is not difficult to make various modifications to these embodiments without departing from the principles and spirit of the present invention. Therefore, the present invention is not limited to the embodiments herein. The improvements and changes made by those skilled in the art to the present invention according to the principles and spirit of the present invention should be within the protection scope of the present invention.

Claims

1. A composite silver plating method for aluminum-based surface of electrical contact components, wherein: The method includes: Surface treatment of the aluminum-based surface of the electrical contact component; Pre-plating a copper layer on the aluminum-based surface of the electrical contact component that has undergone surface treatment; The silver-graphene composite layer is plated on the aluminum-based surface of the electrical contact component that has been pre-plated with a copper layer.

2. The method according to claim 1, wherein: The surface treatment of the aluminum-based surface of the electrical contact component includes: grinding, etching, electro-cleaning and activating the aluminum-based surface of the electrical contact component in sequence; The etching process includes sequentially performing a hydrochloric acid immersion process and an alkaline solution immersion process.

3. The method according to claim 1, wherein: The pre-plated copper layer is carried out by brush plating. The raw materials of the electroplating solution used for the pre-plated copper layer include: CuSO4·5H2O, H2SO4, CuCl2 and solvent. Based on the volume of the electroplating solution, the content of CuSO4·5H2O is 150-180g·L -1 , H2SO4 content is 75-95g·L -1 , CuCl2 content is 0.05-0.15g·L -1 ; Preferably, the solvent in the electroplating solution used for the pre-copper plating layer is water.

4. The method according to claim 3, wherein: During the pre-copper plating process, the working voltage of the brush plating is 6-8V, and the relative movement speed between the brush plating pen and the workpiece is 2-4m·min -1 , current density is 0.1-0.5A·dm -2 , the electroplating time is 2-4min.

5. The method according to any one of claims 1, 3 and 4, wherein: The thickness of the copper layer is 18-25 μm.

6. The method according to claim 1, wherein: The silver-graphene composite layer is plated by brush plating. The raw materials of the plating solution used for the silver-graphene composite layer include: silver nitrate, succinimide, potassium pyrophosphate, graphene and solvent. Based on the volume of the plating solution, the content of silver nitrate is 30-50g·L -1 , the content of succinimide is 20-30g·L -1 , graphene content is 5-30g·L -1 , the content of potassium pyrophosphate is 30-50g·L -1 ; Preferably, the solvent is water.

7. The method according to claim 6, wherein: During the silver-graphene composite layer plating process, the working voltage of the brush plating is 3-5V, and the relative movement speed between the brush plating pen and the workpiece is 2-4m·min -1 , current density is 0.1-0.5A·dm -2 , the electroplating time is 2-4min.

8. The method according to claim 6, wherein: The graphene is modified by using a silane coupling agent; the silane coupling agent is KH570 silane coupling agent.

9. The method according to any one of claims 1, 6-8, wherein: The thickness of the silver-graphene composite layer is 30-37.5 μm.

10. The method according to claim 1, wherein: The composite silver plating method for the aluminum-based surface of the electrical contact component also includes: performing electrolytic passivation treatment on the aluminum-based surface of the electrical contact component that has been plated with a silver-graphene composite layer.

Citation Information

Cited By

  • Graphene composite copper material and preparation method thereof

    CN122169176A